Breakfast to honor the 2005 Provost Fellows. Photo 103 - Leonard, Spencer (Tufts Archival Research Center, 2008)
Breakfast to honor the 2005 Provost Fellows. The Provost's Fellowship program attempts to recruit and recognize the very best incoming doctoral students by providing a supplemental stipend of 5,000 per year. Tufts currently has 25 fellows across the University.